Adsorption Kinetics and Process Parameter Effects on Oil Uptake by Tamarind Fruit-Shell Activated Carbon - Ernawati, Lusi; Anifah, Eka Masrifatus; Musyarofah, Musyarofah; Reza, Mutia; Waluyo, Joko; Sapawe, Norzahir (Politeknik Negeri Malang, 2025)
Oil contamination presents a major challenge to wastewater treatment systems due to its detrimental effects. This research explores the effectiveness of activated carbon derived from tamarind fruit shells as an adsorbent for removing oil from wastewater. The activated carbon was prepared using three different chemical agents: phosphoric acid, zinc chloride, and sodium hydroxide. Characterization of the resulting carbon materials was performed using XRD, FTIR, SEM, and BET analysis. Batch adsorption experiments were conducted to evaluate the influence of initial oil concentration, adsorbent dosage, contact time, temperature, and pH. The BET specific surface area, pore size and total pore volume for the optimum adsorption capacity of activated carbon using H3PO4 are obtained at 617.59 m2.g-1, 37.14 cm3.g-1 and 0.812 g.g-1, respectively. Optimal adsorption occurred at an oil concentration of 5000 mg.L-1, a dosage of 1 g.L-1, a contact time of 60 minutes, a temperature of 60°C, and neutral pH (7). Across all activating agents, the Langmuir isotherm best described the adsorption equilibrium, while adsorption kinetics followed the pseudo-second-order model. Among the samples, activated carbon treated with H3PO4 demonstrated the highest adsorption capacity (1070 mg.g-1), followed by ZnCl2 (879 mg.g-1), and NaOH (643 mg.g-1). These results indicate that tamarind shell-derived activated carbon is a cost-effective and efficient solution for oil removal in wastewater treatment applications.